Saddlepoint method for pricing European options under Markov-switching Heston's stochastic volatility model - Mengzhe Zhang; Leunglung Chan (Journal of Risk and Financial Management, 2022)
This paper evaluates the prices of European-style options when dynamics of the underlying asset is assumed to follow a Markov-switching Heston's stochastic volatility model. Under this framework, the expected return and the long-term mean of the variance of the underlying asset rely on states of the economy modeled by a continuous-time Markov chain. There is evidence that the Markov-switching Heston's stochastic volatility model performs well in capturing major events affecting price dynamics. However, due to the nature of the model, analytic solutions for the prices of options or other financial derivatives do not exist. By means of the saddlepoint method, an analytic approximation for European-style option price is presented. The saddlepoint method gives an effective approximation to option prices under the Markov-switching Heston's stochastic volatility model.
Keywords: 650; European-style options; Markov chain; Markov-switching Heston’ s stochastic volatility model; saddlepoint method